"When five years pass": Federico García Lorca and the problem of the tragic - Castro Filho, Claudio (Tropelías: Review of Literary Theory and Comparative Literature, 2020)
Although Federico García Lorca's re-reading of the greek tragedy is embodied in his famous rural trilogy, his avant-garde works have an acute questioning of the philosophical sense of the tragic in the recent imaginary. When five years pass(1931), part of its cycle of "unrepresentable comedies", expresses a complex philosophical research on the subject tragic. On the one hand, the work is worth a dream environment of surreal court and a deconstruction of subjective categories very to the expressionist taste, revealing the strong dialogue of the author with the European avant-garde . On the other, beside of the form there is a philosophical reflection connected with seemingly disparate universes, as are the auto sacramental of the Siglo de Oro and the reflections on the tragic of Nietzsche and Unamuno. This chapter proposes to break down this problem in Lorca's work, seeking to understand some of the coincidences and discrepancies between the old tragic model and the new approaches to the tragedy of an avant-garde dramaturgy.
Keywords: Federico García Lorca; When five years pass; unrepresentable comedies; Baroque inheritance; tragedy; tragic